Preface - Quayum, Mohammad Abdul (Bangla Prakash, 2017)
Introduces Atiqur Rahman, discusses his poems and explains the techniques used in translating them from Bengali to English. The central themes of Atiqur Rahman's poems are discussed in certain detail.